Hot biopsy for right colonic polypectomy: an audit of practice and complications in a large teaching hospital. (13th March 2011) - Raine, T; Corbett, G; Cameron, E
Abstract : Introduction: Evidence to guide the selection of techniques for colonoscopic polypectomy remains limited and confusing. Limited evidence suggests that monopolar hot biopsy is associated with an increased risk of postpolypectomy bleeding1 and an increased risk of perforation when used in the right colon.2 Although no clear consensus exists on this topic, a guidance statement endorsed by the British Society of Gastroenterology3 recommended the use of cold snare for small sessile polyps in the right colon, with hot snare used only for larger sessile polyps or pedunculated polyps. The American Society of Gastrointestinal Endoscopy and the American College of Gastroenterologists have also advised caution in the use of hot biopsy in the right colon.4 5 Nevertheless, clinical practice remains varied and inconsistent.6 Methods: The authors interrogated the electronic endoscopy database in our large teaching hospital for information about all colonoscopies performed during a 12-month period. Whenever a polypectomy was recorded, information regarding polyp size, location and method of removal was correlated with histological results and records of complications. Hot biopsies were performed using standardised diathermy settings (Erbe ICC 200, forced coagulation 30 W). Results: A total of 3925 colonoscopies were performed during the 12-month period by 44 endoscopists, including 31 trainees. At least one polypectomy was performed in 1399 patients (36%), and a total of 1463 adenomas were removed from 851 patients (overall adenoma detection rate 21.6%). 1255 polypectomies were performed using hot biopsy; 422 (34%) of these were in the right colon, of which 235 were adenomas and 187 hyperplastic polyps. Removal by hot biopsy accounted for 38% of all right sided adenomas. A single perforation occurred in this series, during resection of an 18 mm pedunculated sigmoid polyp. There were no complications with hot biopsy, giving a perforation rate for hot biopsy in the right colon of 0% (95% CI 0% to 0.66%). Conclusion: Despite fears about safety, hot biopsy in the right colon continues to be frequently practiced. This was associated with no perforations in this large series. However, 44% of lesions removed from the right colon by this technique were hyperplastic polyps. With such a high rate of non-neoplastic lesions, any technique associated with even a small increased risk of perforation requires careful justification. Further data are required to define the safety and role of hot biopsy in the right colon.